Analisis Autentifikasi Dokumen Rekam Medis di RSU Tere Margareth - Pohan, Hana Dhini Julia; Meliala, Sri Agustina; Ilham, Muhammad Adiul (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Medical record is a form of health service documentation. Qualified medical records contain complete data, thus it can be processed into information. Authentication of medical record documents includes a clear name, signature, seal/stamp and initials recorded in the medical record or a code of individual for computerization. This research was conducted to realize the authentication of medical record documents at Tere Margareth General Hospital in 2023. This research was a quantitative research with a cross sectional approach. This research was an analytic form of research using primary data and secondary data with a total sample of 67 respondents selected through a random sampling technique. The results showed that health workers with a good knowledge in the authentication of medical record documents were 35 respondents (52.2%), while 32 respondents (47.8%) had a poor knowledge with p = 0.002 < α = 0.05. The attitudes of health workers towards the authentication of medical record documents were good for 28 respondents (41.8%) and unfavourable for 39 respondents (58.2%) with a value of p = 0.000 < α = 0.05. The actions of health workers towards the authentication of medical record documents were good by 31 respondents (46.3%) and unfavourable by 36 respondents (53.7%) with p = 0.003 < α = 0.05. The conclusion of this research is that knowledge, attitudes and actions are influential in completing the data for the authentication of medical record document. Hence, there are still many incomplete data of medical record authentication at Tere Margareth General Hospital.  Keywords: Authentication, Medical Record  ABSTRAK Rekam medis sebagai bentuk dari pendokumentasian layanan kesehatan. Rekam  medis  yang  berkualitas berisi  data  secara  lengkap, sehingga dapat diolah menjadi sebuah informasi. Autentifikasi dokumen rekam medis berupa nama terang, tanda tangan, cap/stempel dan inisial yang dicatat dalam rekam medis atau kode seseorang untuk komputerisasi. Penelitian ini dilakukan bertujuan untuk mengetahui autentifikasi dokumen rekam medis di RSU Tere Margareth Tahun 2023. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Penelitian ini bersifat analitik dengan menggunakan data primer dan data sekunder dengan total sampel 67 responden menggunakan teknik random sampling. Hasil penelitian menunjukkan Pengetahuan tenaga kesehatan terhadap autentifikasi dokumen rekam medis dari pengetahuan baik sebanyak 35 responden (52,2%) dan pengetahuan kurang baik sebanyak 32 responden (47,8%) dengan nilai p = 0,002 < α = 0,05. Sikap tenaga kesehatan terhadap autentifikasi dokumen rekam medis sikap baik sebanyak 28 responden (41,8%) dan sikap kurang baik sebanyak 39 responden (58,2%) dengan nilai p = 0,000 < α = 0,05. Tindakan tenaga kesehatan terhadap autentifikasi dokumen rekam medis tindakan baik sebanyak 31 responden (46,3%) dan tindakan kurang baik sebanyak 36 responden (53,7%) dengan nilai p = 0,003 < α = 0,05. Kesimpulan dalam penelitian ini pengetahuan, sikap dan tindakan berpengaruh  dalam melakukan pengisian kelengkapan data autentifikasi dokumen rekam medis sehingga masih banyaknya data autentifikasi rekam medis yang belum lengkap di RSU Tere Margareth. Kata Kunci: Autentifikasi, Rekam Medis